Literature-based instruction: a worthwhile approach for the mastery of a second language - Mart, Cagri Tugrul (Penerbit Universiti Kebangsaan Malaysia, 2021)
Literature has the potential to encourage learners to become cognisant of patterns and linguistic features of the language because it creates an environment where the applications of the language can function. A growing body of literature has supported the incorporation of literature in second language teaching on the grounds that literature signifies a wide range of accurate use of the language features that paves the way for learning the target language. The present paper attempted to explore the perceptions of learners about welcoming literature in the language classroom for extending language use. The data presented in this study are from interviews. 60 senior-year ELT students were interviewed to reveal their attitudes towards the inclusion of literature into language teaching. Although a small number of the participants questioned the effectiveness of literature, a large number of the participants enumerated several reasons for the inclusion of literature in language learning. The results of the interview highlight the premise that the incorporation of literature into language teaching is shown to be worthwhile for offering a new language learning experience, creating a medium to promote engagement, providing an avenue for coming to good terms with personal development, building an ethos to enhance accuracy and fluency, and constituting ideal occasions to develop learner autonomy.